The buffering effects of psychological capital on the relationship between physical violence and mental health issues of nurses and personal care assistants working in aged care facilities. Issue 1 (16th January 2023) - Pariona-Cabrera, Patricia; Meacham, Hannah; Tham, Tse Leng; Cavanagh, Jillian; Halvorsen, Beni; Holland, Peter; Bartram, Timothy
Abstract : Purpose: The purpose of this study was to examine the effects of psychological capital on the relationship between physical violence and mental health issues of nurses and personal care assistants (PCAs) working in aged care using the job demands–resources theory. Methodology: Data were collected from 254 nurses and PCAs of the Australian Nursing Midwifery Federation located in Victoria, Australia. The study takes a quantitative approach and tests the hypotheses through regression analyses. Findings: The results indicate that experiencing physical violence increases levels of stress, depression, and anxiety. This, in turn, increases nurses' and PCAs' intention to leave. However, increased psychological capital can assist nurses and PCAs in dealing with physical violence. Research Implications: The study acknowledges that physical violence is a factor in nurses' intention to leave. The significant finding is that psychological capital plays a protective role in ameliorating the negative impact of physical violence on individual well-being and intentions to leave. We note, however, that this is a cross-section study, and more longitudinal research needs to be undertaken. Practical Implications: There are clear implications for managers to create a supportive organization that cultivates hope, self-efficacy, and resilience, thereby increasing psychological capital. Leadership development programs could build a supportive foundation for nurses to seek support and build resilience. Job construction should be focused on protecting nurses from risk by utilizing manageable workloads to limit stress, depression, and anxiety. Originality: Our study extends research on retention of these skilled and important health care workers in a demanding environment that has largely been absent from the literature. Specifically, physical violence is often considered part of nursing work, but its impact on mental health, well-being, and intention to leave are underexplored in this sector, as well as the effectiveness of specific measures that bolster the negative impact of physical violence on nurses.